Evolutionary-Conserved Allosteric Properties of Three Neuronal Calcium Sensor Proteins - Marino, Valerio; Dell'Orco, Daniele (Frontiers in Molecular Neuroscience, 2019)
Neuronal Calcium Sensors (NCS) are highly conserved proteins specifically expressed in neurons. Calcium (Ca2+)-binding to their EF-hand motifs results in a conformational change, which is crucial for the recognition of a specific target and the downstream biological process. Here we present a comprehensive analysis of the allosteric communication between Ca2+-binding sites and the target interfaces of three NCS, namely NCS1, recoverin (Rec) and GCAP1. In particular, Rec was investigated in different Ca2+-loading states and in complex with a peptide from the Rhodopsin Kinase (GRK1) while NCS1 was studied in a Ca2+-loaded state in complex with either the same GRK1 target or a peptide from the D2 Dopamine receptor. A Protein Structure Network (PSN) accounting for persistent noncovalent interactions between amino acids was built for each protein state based on exhaustive Molecular Dynamics simulations. Structural network analysis helped unveiling the role of key amino acids in allosteric mechanisms and their evolutionary conservation among homologous proteins. Results for NCS1 highlighted allosteric inter-domain interactions between Ca2+-binding motifs and residues involved in target recognition. Robust long range, allosteric protein-target interactions were found also in Rec, in particular originating from the EF3 motif. Interestingly, Tyr 86, involved the hydrophobic packing of the N-terminal domain, was found to be a key residue for both intra- and intermolecular communication with EF3, regardless of the presence of target or Ca2+ ions. Finally, based on a comprehensive topological PSN analysis for Rec, NCS1 and GCAP1 and multiple sequence alignments with homologue proteins, we propose that an evolution-driven correlation may exist between the amino acids mediating the highest number of persistent interactions (high-degree hubs) and their conservation. Such conservation is apparently fundamental for the specific structural dynamics required in signaling events.